Teaching Public Relations to Students with a Confucian Cultural Background - HALFF, Jurrien Gregor (Institutional Knowledge at Singapore Management University, 2012)
This paper explores how the Confucian cultural background of students influences their perceptions of and reaction to the dominant public relations curriculum from the ‘West’. Using focus groups of Asian students, three heuristics that affect the students’ affinity to learn public relations are identified. Instructors working with students from a Confucian cultural background are advised to incorporate these heuristics when planning their curriculum.